Effect of Using Apple Cider Vinegar on Foot Ulcer Healing in Patients with Type II Diabetes - Asmaa Kareem Hameed; Fatma Makee Mahmood (Migration Letters, 2023)
Background: Foot ulcers are one of the usual and dangerous complication that occurs in patients with diabetes. In severe cases, diabetic foot lesions cause amputation of the lower extremities. Apple vinegar have an antimicrobial properties and other clinical therapeutic consequences. Objective: This study was performed o examine the apple cider vinegar’s impact on foot ulcer healing in diabetes mellitus patients. Method: A quasi-experimental study was conducted at the Imam Al-Hassan Center for Endocrinology and Diabetes from September 26, 2022, to June 12, 2023. A purposive sample include of sixty patients with diabetic foot ulceration who they were separated randomly into intervention and control group. Patients in the intervention group were instructed to perform foot ulcer irrigation once a day for 30 days, while only routine care was provided to the control group. The study instrument included socio-demographic and clinical data of participants, and the DMIST for observing the process of healing from a diabetic foot ulcer. The instruments were validated by a panel of experts, and itis reliability was verified through a pilot study. Both a descriptive analysis procedure and an inferential analysis procedure (independent sample T-test, repeated measures ANOVA and Chi-square) were used to examine and measure the study findings; a p-value of <0.05 was determined to be statistically relevant. Results: Most (70% and 66.7%) of patients in the control and experimental groups, respectively, had a moderate level of healing at pre-test assessment. Conversely, at the post-test assessment, 80% of patients in the intervention group had good foot ulcer healing, while 16.7% of patients in the control group had good foot ulceration healing. Furthermore, a significant difference at p-value 0,001 noticed among the control and apple cider vinegar irrigation groups. after using apple cider vinegar on foot ulcers. Conclusions: Using apple cider vinegar as foot ulcer irrigation is an effective method for promoting foot ulcer healing among diabetic patients.